Analysis of GNSS correction data standards for the automotive market. Issue 3 (25th July 2019) - Vana, Sudha; Aggrey, John; Bisnath, Sunil; Leandro, Rodrigo; Urquhart, Landon; Gonzalez, Paola
Abstract: In this paper, a new standard that has been developed by Sapcorda Services to target the specific requirements of high‐precision GNSS technology in the automotive and mass market industry is assessed within the context of existing data standards. This new standard was created as a joint effort of several organizations and has similarities with the Radio Technical Commission for Maritime Services (RTCM) v3 standard and compact state‐space representation messages (CSSR). However, it has different message design rules that specifically target automotive and mass market sectors. Results indicate significant reduction in bandwidth usage particularly for the atmosphere component, as the new format consumes 15% less bandwidth compared with the all‐purpose existing formats, increased end‐to‐end positioning performance, and integrity, as well as flexibility for future growth of GNSS correction services.